Drivers of recovery and degradation of riverine benthic invertebrate communities: a Germany-wide analysis - Schürings, Christian; Kaijser, Willem; Gillmann, Svenja M.; Kiesel, Jens; Nguyen, Hong H.; Peters, Kristin; Rolauffs, Peter; Haase, Peter; Lorenz, Armin W.; Hering, Daniel (Ecological processes, 2025)
Background The global freshwater biodiversity crisis has led to widespread implementation of measures to counteract environmental degradation and biodiversity loss. While these efforts aim to foster recovery, intensifying stressors continue to drive complex biotic responses, the trajectories and drivers of which are insufficiently understood. This study examines the roles of abiotic stressors, biotic interactions (e.g., competition), and land use in shaping ecological status changes across Germany, using data from 1599 river sites sampled at least twice between 2004 and 2022. Results Changes in abiotic stressors emerged as the most consistent drivers of ecological status, explaining substantial variation ( R 2 = 0.39) and similar slopes for recovery ( β = − 0.11) and degradation ( β = − 0.10). Biotic interactions, particularly interspecific competition, also influenced the ecological status ( R 2 = 0.11), with stronger positive effects observed during recovery ( β = 2.99) compared to degradation ( β = 1.59). Land use effects varied by context: Streams in catchments with higher cropland or urban areas showed greater likelihood of recovery, whereas streams in forested catchments were more prone to degradation. These results highlight the interplay of abiotic and biotic factors in driving ecological processes of recovery and degradation. Conclusion These findings emphasize the critical role of improving water quality for enhancing biodiversity and ecological status in rivers, while also demonstrating the importance of biotic interactions and land use context in driving recovery dynamics. Integrating these insights into management and restoration efforts can enhance freshwater ecosystem resilience in the face of escalating environmental pressures.